Raising a technology addict: virtual environment as an emotion regulation tool from infancy till adolescence - Karateke, Başak (Journal of Dependence, 2020)
Technology has started to play a facilitating role in the field of parenting after the fields of entertainment, education, health. However, the support of the virtual environments to the parents may cause technology addiction. The virtual environments which make activities and entertain children previously, has become to share responsibilities with parents. The aim of this review is to discuss the role of the over use of technology, which is accepted as helpful assistants by the parents, in childhood through the term of emotional regulation. The concept of emotional regulation is defined as the individual’s appropriate emotional response to the stimulus. The related studies show that the processes of attachment and accordingly the parent-child relationship have importance in the development of the skill of emotional regulation. The negative emotions that should be regulated by the parents during the child nutrition or medical examination, have been regulated by the virtual environments such as smartphone or tablet instead of parents.
Keywords: Technology addiction; emotional regulation; attachment process